2023
DOI: 10.1136/bmjopen-2022-062688
|View full text |Cite
|
Sign up to set email alerts
|

Nudge interventions to reduce unnecessary antibiotic prescribing in primary care: a systematic review

Abstract: ObjectivesAntibiotic prescribing in primary care contributes significantly to antibiotic overuse. Nudge interventions alter the decision-making environment to achieve behaviour change without restricting options. Our objectives were to conduct a systematic review to describe the types of nudge interventions used to reduce unnecessary antibiotic prescribing in primary care, their key features, and their effects on antibiotic prescribing overall.MethodsMedline, Embase and grey literature were searched for random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A similar study in the United Kingdom found an approximate 5% reduction in antimicrobial prescribing when letters were sent to primary care physicians in the top 20% of antimicrobial prescribers. 54 Although the literature is mixed, 55 peer comparison remains a relatively low-intensity intervention to reduce antimicrobial exposure at scale. Developing peer-comparison interventions that target prescribers in the top 3 quartiles, rather than only the highest quartile or outliers, may help further reduce antimicrobial prescribing in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in the United Kingdom found an approximate 5% reduction in antimicrobial prescribing when letters were sent to primary care physicians in the top 20% of antimicrobial prescribers. 54 Although the literature is mixed, 55 peer comparison remains a relatively low-intensity intervention to reduce antimicrobial exposure at scale. Developing peer-comparison interventions that target prescribers in the top 3 quartiles, rather than only the highest quartile or outliers, may help further reduce antimicrobial prescribing in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…These published systematic reviews cover a wide range of behaviors. These include healthy food choices 25,[29][30][31][32][33][34][35][36][37][38][39] , dietary behaviors [40][41][42][43][44] , other health related behaviors 36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] , environmental behaviors [61][62][63][64][65][66][67] , disclosure of personal information 68 , tax compliance 69 , learning behavior 70 and children's sleep 71 . Additionally, some of the reviews address various types of interventions such as digital nudges 72 or default options 73 .…”
Section: The Case Of Inflated Effect Sizesmentioning
confidence: 99%
“…Nudge interventions are attempts to shape behaviors through subconscious attitudes or routines that influence decision making 7. Nudge interventions have been found to be useful in a variety of decision processes, including antibiotic prescribing and hand hygiene 89. Important methodological considerations underlie the application of nudge strategies to doctors’ sitting behavior, including questions about whether the study design and nudge can account for other salient dynamics that shape patients’ perceptions of communication.…”
Section: Chair Placementmentioning
confidence: 99%